Young people and mountain - Andrea Macchiavelli; Andrea Pozzi (Revue de Géographie Alpine)
The active frequentation of mountain areas has been analysed especially in relation with the territory and the landscape. This paper presents the results of an extensive research project carried out in Northern Italy that investigated the relationship between people and mountain focusing especially on younger generations, and highlights the conditions and the expectations towards mountain hiking in the Alps both in summer and winter. The analysis was carried out by: an overview of existing literature on the subject, with particular reference to Italy; a direct CATI survey on a population sample; a direct survey on a sample of students from high schools; in-depth interviews with guides from the Youth Mountaineering Commissions of Club Alpino Italiano (CAI). The paper will present a reasoned synthesis of the work done, with the aim to bring out the main factors that characterize the relationship between young people and mountain hiking.